Modern Minimalist Shelf Inspired by White Luxury - Budjang, Muhamad Huzairi; Selimin, Mohamad Ali; Md Rawi, Muhammad Firdaus (Research in Management of Technology and Business, 2022)
Bulky shelves are frequently heavy, especially when made of solid materials such as solid wood and thick tempered glass, needing the use of two or more people to transfer them from one location to another. Furthermore, if the furniture is an elegant, antique armoire, it will not only be enormous and weighty but also delicate and precious, necessitating extra care. Thus, the objective of this study is to design and develop a modern minimalist shelf inspired by the white luxury that is portable. To begin, the design criteria for this study were acquired using a questionnaire issued via Google Form. According to the survey, the majority of respondents favoured bookshelf with a modern design and segregated storage space. During the design process, 35 thumbnails, four ideations, and three concept developments were drawn. The final prototype for this study was made of plywood with white stickers and acrylic plastics. Although the newly designed bookshelf solves the aforementioned issue, there are a few design changes that may be made to increase its value and aesthetic.